Quality-Oriented Teacher Recruitment for Sustainable Development Goals (SDGs) Education in Developing Countries - Anggal, Nikolaus (Educationist: Journal of Educational and Cultural Studies, 2022)
The purpose of this study was to understand the potential use of resource management theory and practice in recruiting teachers who are oriented towards the quality and quality of education. This study uses a qualitative approach with a literature study method. Through this literature study, the authors analyze how the management of teacher recruitment in Indonesia is to obtain a recruitment strategy that is oriented to the quality or quality of education. The results of this study found that the needs of teachers in schools in Indonesia are different so that various recruitment management processes have been utilized, both by the central government, local governments, and school principals. The results of this study also provide a strong rationale for further research to demonstrate the great potential of harnessing expertise in quality-based teacher recruitment to lead to future improvements in the quality of education. The solutions to the obstacles faced in the recruitment process are, (1) the central government improves coordination and close cooperation with local governments to make teacher redistribution more evenly and ensure teacher recruitment is carried out following the needs at the education unit level; (2) develop teacher performance standards based on measurable and comprehensive competencies and use these standards in developing teacher recruitment instruments, training programs, and performance evaluations. The findings of this study reinforce recent literature that identifies the teacher recruitment process as the basis for improving the quality of education.